PERBANDINGAN PEMIKIRAN SISTEM EKONOMI ISLAM ANTARA ABU A’LA AL-MAUDUDI DAN TAQIYUDDIN AN-NABHANI - Aziz, Rifan Abdul; Juliana, Juliana; Firmansyah, Firmansyah (PT. Student Rihlah Indonesia, 2022)
The reason is that these two figures not only have a complete, ideal, philosophical, and original concept of Islamic economic system thinking, but also these two figures are among the first to write a book related to the Islamic economic system in modern history. The two figures are Abu A'la Al-Maududi and Taqiyuddin An-Nabhani. This research is a qualitative research and the research method used is the study of literature. The research data are books by the two figures related to the Islamic economic system. The results of the study show that their thoughts on Islamic economics are not pragmatic and ideal, substantial, and philosophical and there are two basic differences in their thoughts on the Islamic economic system and three differences that can be tolerated and the similarities between the two are quite a lot of differences and similarities between the two reflect that The thought of the Islamic economic system is both different from the capitalist economic system.